2016
DOI: 10.1002/advs.201600168
|View full text |Cite
|
Sign up to set email alerts
|

Towards High‐Safe Lithium Metal Anodes: Suppressing Lithium Dendrites via Tuning Surface Energy

Abstract: The formation of lithium dendrites induces the notorious safety issue and poor cycling life of energy storage devices, such as lithium–sulfur and lithium–air batteries. We propose a surface energy model to describe the complex interface between the lithium anode and electrolyte. A universal strategy of hindering formation of lithium dendrites via tuning surface energy of the relevant thin film growth is suggested. The merit of the novel motif lies not only fundamentally a perfect correlation between electroche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
269
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 449 publications
(284 citation statements)
references
References 103 publications
3
269
0
5
Order By: Relevance
“…[144][145][146][147] However, this strategy loses 90% of the capacity contributing from Li metal anode and now cannot satisfy the urgent demand of high energy density devices. Exploring an efficient host for Li metal anode is quite crucial for a practical Li−S battery.…”
Section: Metal Protection In Li−s Batteriesmentioning
confidence: 99%
“…[144][145][146][147] However, this strategy loses 90% of the capacity contributing from Li metal anode and now cannot satisfy the urgent demand of high energy density devices. Exploring an efficient host for Li metal anode is quite crucial for a practical Li−S battery.…”
Section: Metal Protection In Li−s Batteriesmentioning
confidence: 99%
“…[6][7][8][9][10] Unfortunately, the uneven plating/stripping of Li metal causes uncontrolled Li dendrite growth, which induces a series of problems. [6][7][8][9][10] Unfortunately, the uneven plating/stripping of Li metal causes uncontrolled Li dendrite growth, which induces a series of problems.…”
mentioning
confidence: 99%
“…In addition, unstacked graphenes with a hexagonal‐drum like morphology can reduce the effective current density of the electrode, regulate Li deposition, and suppress dendrite formation . Most studies were aimed at developing large surface area porous hosts to reduce the local current density and thus inhibit dendrite formation according to the classical theory of dendrite growth . However, recent studies have shown that porous hosts with a large electroactive surface area are helpful in reducing the nucleation overpotential and producing uniform Li deposition .…”
Section: Strategies For Developing Stable LI Metal Anodesmentioning
confidence: 99%